On the Theoretical Features of the Political Economy of Socialism with Chinese Characteristics and the New Issues. (14th October 2022) - He, Zili
Abstract : Marxist political economy possesses a unique theoretical quality, and provides deep insights into the laws of social development and the progress of human society. The political economy of socialism with Chinese characteristics is the product of combining the fundamentals of Marxist political economy with the practice of the economic construction of socialism with Chinese characteristics; it also plays an important role in guiding China as it records economic achievements that are attracting worldwide attention. Socialism with Chinese characteristics has entered a new era, in which the political economy of socialism with Chinese characteristics is being called upon to deal with a series of new issues as well as to make new contributions to promoting the construction of socialist modernization and the cause of reform and opening-up.